Update on the human broad tapeworm (genus diphyllobothrium), including clinical relevance - Scholz, Tomás; Garcia, Hector H; Kuchta, Roman; Wicht, Barbara (Clinical microbiology reviews, 2009)
Tapeworms (Cestoda) continue to be an important cause of morbidity in humans worldwide. Diphyllobothriosis, a human disease caused by tapeworms of the genus Diphyllobothrium, is the most important fish-borne zoonosis caused by a cestode parasite. Up to 20 million humans are estimated to be infected worldwide. Besides humans, definitive hosts of Diphyllobothrium include piscivorous birds and mammals, which represent a significant zoonotic reservoir. The second intermediate hosts include both freshwater and marine fish, especially anadromous species such as salmonids. The zoonosis occurs most commonly in countries where the consumption of raw or marinated fish is a frequent practice. Due to the increasing popularity of dishes utilizing uncooked fish, numerous cases of human infections have appeared recently, even in the most developed countries. As many as 14 valid species of Diphyllobothrium can cause human diphyllobothriosis, with D. latum and D. nihonkaiense being the most important pathogens. In this paper, all taxa from humans reported are reviewed, with brief information on their life history and their current distribution. Data on diagnostics, epidemiology, clinical relevance, and control of the disease are also summarized. The importance of reliable identification of human-infecting species with molecular tools (sequences of mitochondrial genes) as well as the necessity of epidemiological studies aimed at determining the sources of infections are pointed out.
Keywords: zoonózy; Fishes; zvířata; Diphyllobothriasis; Humans; ryby; ptáci; Birds; Mammals; difylobotriáza; savci; Zoonoses; lidé; Diphyllobothrium; Animals